Green approach to functionalize highly stable graphene nanoplatelet colloid for heat-based applications / Siti Shafiah Shazali - Siti Shafiah , Shazali (2019)
In recent years, research efforts on the functionalization of graphene nanoplatelets (GNPs) have intensified due to the promisingly improved physical features and properties inherent within the modified structure that broaden its functionalities to suit diverse applications. In this research work, both covalent and non-covalent functionalization methods were applied on GNPs nanomaterials to enhance their stability and thermophysical attributes. Further investigation on the material performance based on different parameters in engineering applications (i.e., heat transfer and thermoelectrochemistry) was also carried out in this research. Researchers over the years have gone through the modification of GNPs structure in order to increase their colloidal stability to be used in specific applications. However, most of the studies involved hazardous chemicals and complex approaches. In this light, the focus of this research is directed toward the functionalization of GNPs material in a more environmentally friendly and facile method. Under covalent functionalization scheme, GNPs were derivatized with polymer and sugar alcohol using esterification process as well as subjected to doping process with nitrogen. On the other hand, a solvent-friendly surfactant with enhanced physical properties was chosen as the coating material for GNPs under non-covalent functionalization approach. A series of characterizations using spectroscopy, imaging, and electrophoresis instruments were conducted in order to examine the morphological structure, resolve the bond of functional groups, and also measure the colloidal stability of the functionalized GNPs. Thermal conductivity and viscosity properties in aqueous media improved significantly by using the functionalized GNPs. Finally, the functionalized GNPs materials were used as a solid additive in an aqueous solution that serves as heat transport media to improve the convective heat transfer performance under constant heat flux. Meanwhile, in thermoelectrochemistry application, the treated-GNPs materials were used as an additive in a redox solution to increase the electrical performance with the increase of temperatures. All of the functionalized samples showed improved performance for the mentioned applications.